Making the case for a resurgent U.S. independent veterinary practice segment: a SWOT analysis - Traub-Werner, Martin; Salois, Matthew; McKay, Charlotte; Platt, Marne (Frontiers in Veterinary Science, 2025)
Private equity and corporate ownership of veterinary practices has largely been characterized as either wholly good or wholly bad. Supporters point to increased returns and access to capital and investments in associates, technology, and other resources. Opponents point to unnecessary debt and decreased quality of care. Good or bad, they are part of the practice landscape. This SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis of independent veterinary practice reveals that, while corporate veterinary practices have a role, a thriving independent practice segment still provides a deeply satisfying career and a viable living. We conclude that, with the current economic conditions and the appropriate modifications in the veterinary ecosystem, conditions are ripe for a resurgence of independent veterinary practice ownership.